PRODUCT EXCELLENCE AND SERVICE EFFECTIVENESS AT BSI: KEY TO CUSTOMER LOYALTY OF EASY WADIAH PRODUCTS - Supriadi; Ahmad, Nur Isra' (Journal of Islamic Studies [Z-ISLAMICA], 2025)
This study aims to find and analyze the influence of product excellence and service effectiveness on customer loyalty in easy wadiah savings products at Bank Syariah Indonesia Makassar Branch. This type of research is quantitative, with 34 respondents from Bank Syariah Indonesia Makassar Branch with a sampling technique using probability sampling. The data collection instrument uses a closed questionnaire with a Likert scale. The quantitative analysis uses SPSS (Statistical Product and Service Solution). The results of this study indicate that product excellence and service effectiveness positively and significantly influence customer loyalty in using easy wadiah savings at Bank Syariah Indonesia Makassar Branch. This finding indicates that Bank Syariah Indonesia needs to maintain product excellence and strengthen service effectiveness so that customers remain loyal.